B. D. Karvasarsky and psychotherapy establishment as a distinct discipline, homo faber, to the 90-th anniversary since birth - A. V. Vasileva; T. A. Karavaeva; E. B. Mizinova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
The establishment of psychotherapy and clinical psychology in a Russia is a very complicated and contradictive process. B. D. Karvassarsky has played an essential, key role in the psychotherapy formation as a science and distinct discipline. The article describes the crucial points of this discipline development, presents the main key studies of this mental health field. The Leningrad-Saint-Petersburg psychotherapy school maid a serious impact in the modern Russian neurosology cornerstone issues, that allowed to consider the multidimensional aspects of this pathology. This publication emphasizes the recent research results in this field, makes a deep analysis of the target phenomena understanding in different approaches, other methods integration in personality oriented reconstructive psychotherapy, elaboration of the nosocentric target oriented psychotherapy algorithms and strategies, and also different psychotherapy interventions research.